The Effect Of Audit Committee Characteristics On Audit Quality: The Moderating Role Of Internal Audit Function - Josephine Kuan Pei See; Anwar Allah Pitchay; Yuvaraj Ganesan; Hasnah Haron; Ratih Hendayani (Universiti Malaysia Pahang, 2024)
Volume :3 No:2